Moving towards an Outcomes-Oriented Approach to Nutrition Program Monitoring : The India ICDS Program - Adhikari, Saroj K.; Bredenkamp, Caryn (World Bank, Washington, DC, 2013)
Focusing on the Integrated Child Development Services (ICDS), India's largest nutrition and early child development program, this paper describes the political, organizational, and technical challenges in building and sustaining an outcomes-oriented approach to nutrition program monitoring. The author show that the current policy environment appears to be conducive to strengthening nutrition program monitoring: political commitment is growing, financial allocations to ICDS have increased and, recently, a number of reforms to strengthen the ICDS monitoring and evaluation system have been undertaken. Yet, substantial weaknesses remain. This paper discusses some of the challenges in converting this vision into action and suggests some immediate steps that could be considered both at the central and state levels.